Human Papillomavirus 16 Lineage D is Associated with High Risk of Cervical Cancer in the Brazilian Northeast Region - Martins, Luís Felipe Leite; Moreira, Miguel Ângelo Martins; Pinto, Rodrigo Alves; Reis, Neilane Bertoni dos; Felix, Shayany Pinto; Vidal, João Paulo Castello Branco; Torres, Leuridan Cavalcante; Souza, Ariani Impieri; Almeida, Liz Maria de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective Similar to Human Papillomavirus (HPV) genotypes, different lineages of a genotype also have different carcinogenic capabilities. Studies have shown that specific genotype lineages of oncogenic HPV are associated with variable risks for the development of cervical intraepithelial neoplasia (CIN2/CIN3) and cervical cancer. The present study aimed to analyze the genetic diversity of the HPV16 genotype in women with CIN2/CIN3 and cervical cancer, from the northeast region of Brazil.Methods A cross-sectional multicenter study was conducted in the northeast region of Brazil, from 2014 to 2016. This study included 196 cases of HPV16 variants (59 and 137 cases of CIN2/CIN3 and cervical cancer, respectively). The difference of proportion test was used to compare patients with CIN2/CIN3 and cervical cancer, based on the prevalent HPV16 lineage (p < 0.05).Results According to the histopathological diagnosis, the percentage of lineage frequencies revealed a marginal difference in the prevalence of lineage A in CIN2/CIN3, compared with that in cervical cancer (p = 0.053). For lineage D, the proportion was higher in cancer cases (32.8%), than in CIN2/CIN3 cases (16.9%), with p = 0.023.Conclusion HPV16 lineage A was the most frequent lineage in both CIN2/CIN3 and cervical cancer samples, while lineage D was predominant in cervical cancer, suggesting a possible association between HPV16 lineage D and cervical cancer.
Keywords: HPV16; lineage A; lineage D; CIN2/CIN3; cervical cancer